Pelatihan Penggunaan Media Kadot dalam Pembelajaran Penjumlahan dan Pengurangan Bilangan Tiga Angka Bagi Siswa Kelas III SDN 2 Alas Sumur Kulon Kabupaten Probolinggo - Saila, Nurul; Uswatun Hasanah; Dita Ananda Carolina; Ilse Yulia Rizti (Jurnal Pengabdian Ahmad Yani, 2023)
The level of intellectual development of elementary school (SD) students is at the concrete operational level. At the concrete operational level, children are able to think logically, but can only apply logic to physical objects. So in studying mathematics which has an abstract nature, assistance is needed using learning media. The ability to determine the results of adding and subtracting three-digit numbers is an ability that must be mastered by third grade elementary school students. This ability is one of the basic abilities in calculating, so the student's inability will affect the student's ability to understand further elementary mathematics material. The problem that arises at SDN 2 Alas Sumur Kulon, Probolinggo Regency is that many class III students experience difficulties in learning to add and subtract three-digit numbers, because the teacher does not use media in their learning. The aim of this activity is to help class III students at SDN 2 Alas Sumur Kulon master the skill of determining the results of adding and subtracting three-digit numbers using the medium of khast (a number bag and a straw). This community service activity includes three stages of activity, namely the preparation stage, training implementation and evaluation. The achievements of this community service activity are (1) 86,674% of training participants obtained a final test score higher or equal to the KKM; (2) the level of participant satisfaction with training activities is 100%; and (3) 100% of the training participants stated that the training in using the gift medium to determine the results of adding and subtracting three-digit numbers helped them master the skill of determining the results of adding and subtracting three-digit numbers. Keywords: Training, Kadot Media, Addition and Substractions.